The effect of nano-selenium in mitigating the oxidative effects of lead on date palms (Phoenix dactylifera L.) - Mahdi, Ali S; Al-Hamoud, Firas M (Basrah Journal Of Date Palm Research, 2025)
This study aimed to evaluate the role of nano-selenium (Se NPs) in alleviating oxidative stress induced by lead contamination in date palm (Phoenix dactylifera L.). The experiment was conducted using a randomised complete block design, in which four lead concentrations (0, 50, 100 and 150 mg L⁻¹) and three concentrations of Se NPs (0, 100 and 200 mg L⁻¹) were applied as foliar sprays to three-year-old date palm trees over a six-month period. The results demonstrated that increasing lead concentration caused a significant reduction in chlorophyll content and total proteins, accompanied by a significant increase in amino acids, compatible solutes, and oxidative stress indicators, including hydrogen peroxide and malondialdehyde (MDA). In addition, the membrane stability index (MSI) declined, while the activities of enzymatic and non-enzymatic antioxidants increased. In contrast, the application of Se NPs, particularly at 100 mg L⁻¹, markedly mitigated these adverse effects by enhancing antioxidative defence mechanisms. This was evidenced by increased activities of catalase (CAT) and peroxidase (POD), enhanced accumulation of compatible solutes such as proline, glycine betaine and carotenoids, and the maintenance of total protein and chlorophyll contents. Furthermore, the results indicated that the moderate concentration of Se NPs (100 mg L⁻¹) was the most effective, whereas the higher concentration (200 mg L⁻¹) exerted detrimental stress effects. Overall, the findings suggest that nano-selenium represents a promising strategy for enhancing the tolerance of date palm to heavy metal stress, particularly lead.